Mapuche Children’s Play on the Playground in a Rural School - Alonqueo Boudon, Paula; Loncón Raín, Maribel; Vásquez Moreno, Fabiola; Gutiérrez, Javiera; Parada Silva, Loreto (Revista de Psicología, 2017)
Children’s play is a culturally structured activity in which relevant cultural content is implicitly and explicitly represented (Lancy, 2015). The school is a space of fundamental socialization where varied social interactions occur, being those happening in the playground of vital relevance. The objective of this research was to describe the characteristics of play in the playground of Mapuche children attending a rural school in the commune of Freire, Araucanía Region. A total of 16 children between 6 and 12 years old participated in this study. An ethnographic approach was used employing open observation to register 6 break episodes. The results indicated that the type of play observed is mainly non-competitive and exercise, with group interaction predominating among children of different ages, even though it was observed that boys and girls tend to ignore each other. The rules of the observed plays were generally implicit and artifacts were used for the purpose of sharing with other children. These findings are discussed based on the concept of constellations of cultural practices identifying characteristics of the Mapuche culture.